Combination therapy of IFNβ1 with lopinavir–ritonavir, increases oxygenation, survival and discharging of sever COVID-19 infected inpatients - Baghaei, Parvaneh (Int Immunopharmacol, 2021)
Interferon Beta-1a (IFN-β1-a), an immunomodulatory mediator with antiviral effects, has shown in vivo and in vitro activities especially on coronavirus including SARS-CoV-2. COVID-19 defined as the disease caused by infection with SARS-CoV-2. The virus has been illustrated inhibits the production of IFN-β1-a from inflammatory cells. We conducted a retrospective study of all adult confirmed COVID-19 hospitalized patients who received combination of three doses of 12 million international units of IFN-β1-a and Lopinavir 400 mg and Ritonavir 100 mg every 12 h (case group) for 14 days besides standard care and age- and sex- matched COVID-19 patients with receiving lopinavir/ritonavir (control group) at Masih Daneshvari Hospital as a designated hospital for COVID-19 between Feb 19 and Apr 30, 2020. Multivariate analysis was done to determine the impact of IFN-β1-a on outcome and all-cause mortality. 152 cases in IFN-β1-a group and 304 cases as control group were included. IFN-β1-a group stayed at hospital longer and required noninvasive ventilation more than control group (13 vs. 6 days, p = 0.001) and (34% vs. 24%, p = 0.04), respectively. During treatment, 57 (12.5%) patients died. The death rate in case and control groups was 11% and 13% respectively. In multivariate analysis, not receiving IFN-β1-a (HR 5.12, 95% CI: 2.77–9.45), comorbidity (HR 2.28, 95% CI: 1.13–4.60) and noninvasive ventilation (HR 2.77, 95% CI: 1.56–4.93) remained significantly associated with all-cause mortality. In this study, risk of death decreased by using IFN-β1-a in COVID-19 patients. More clinical study will be necessary to measure efficacy of IFN-β1-a in COVID-19 treatment.